Energy Harvesting from Human Motion Using Footstep-Induced Airflow. (November 2015) - Fu, H; Xu, R; Seto, K; Yeatman, E M; Kim, S G
Abstract: This paper presents an unobtrusive in-shoe energy harvester converting foot-strike energy into electricity to power wearable or portable devices. An air-pumped turbine system is developed to address the issues of the limited vertical deformation of shoes and the low frequency of human motion that impede harvesting energy from this source. The air pump is employed to convert the vertical foot-strike motion into airflow. The generated airflow passes through the miniaturized wind turbine whose transduction is realized by an electromagnetic generator. Energy is extracted from the generator with a higher frequency than that of footsteps, boosting the output power of the device. The turbine casing is specifically designed to enable the device to operate continuously with airflow in both directions. A prototype was fabricated and then tested under different situations. A 6 mW peak power output was obtained with a 4.9 Ω load. The achievable power from this design was estimated theoretically for understanding and further improvement.